2023
DOI: 10.3389/fonc.2022.1088458
|View full text |Cite
|
Sign up to set email alerts
|

The Uridine diphosphate (UDP)-glycosyltransferases (UGTs) superfamily: the role in tumor cell metabolism

Abstract: UDP-glycosyltransferases (UGTs), important enzymes in biotransformation, control the levels and distribution of numerous endogenous signaling molecules and the metabolism of a wide range of endogenous and exogenous chemicals. The UGT superfamily in mammals consists of the UGT1, UGT2, UGT3, and UGT8 families. UGTs are rate-limiting enzymes in the glucuronate pathway, and in tumors, they are either overexpressed or underexpressed. Alterations in their metabolism can affect gluconeogenesis and lipid metabolism pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…More importantly, we constructed the upstream and downstream regulatory networks of SRSF, which provided a reference for revealing the mechanism of SRSF in tumorigenesis and development. In this study, GSEA analysis showed that SRSF were mainly associated with oncogenic pathways including galactose metabolism pathway, which leading to alterations in tumor cell metabolism and affecting cancer development, growth, and survival (Liu et al, 2022). Pathway enrichment analysis indicated that the SRSF family was involved in the upregulation of tumor metabolism and metastasis, which provided novel clues for further exploration for the molecular mechanisms of SRSF in DLBCL.…”
Section: Discussionmentioning
confidence: 71%
“…More importantly, we constructed the upstream and downstream regulatory networks of SRSF, which provided a reference for revealing the mechanism of SRSF in tumorigenesis and development. In this study, GSEA analysis showed that SRSF were mainly associated with oncogenic pathways including galactose metabolism pathway, which leading to alterations in tumor cell metabolism and affecting cancer development, growth, and survival (Liu et al, 2022). Pathway enrichment analysis indicated that the SRSF family was involved in the upregulation of tumor metabolism and metastasis, which provided novel clues for further exploration for the molecular mechanisms of SRSF in DLBCL.…”
Section: Discussionmentioning
confidence: 71%
“…Also, high levels of 4-OH-tamoxifen-N-glucuronide were observed in the blood plasma of UGT2B17del genotype carriers, which can be attributed to a mechanism that compensates for the higher expression of other genes in UGT2B17 del/del carriers [30]. In addition, studies have shown that the activity of UGT1A10 and UGT2B7 was reduced in malignant breast tumors compared with the corresponding enzymes in normal breast tissues [7,10,27,20]. Also, the glucuronidation activity of estradiol, the most physiologically active form of estrogen, was reduced in most cases of breast cancer compared to normal breast tissue [11,14,27].…”
Section: Results Discussionmentioning
confidence: 99%
“…(Meech et al, 2015). Through glucuronidation process, UGTs weaken the biological activity of these drugs or chemical substances and increases their water solubility; hence, driving them to be eliminated in bile, urine and feces (Liu et al, 2023). Human UGTs are expressed in a wide range of organs and tissues.…”
Section: Insects and Glycosyltransferasesmentioning
confidence: 99%
“…Human UGTs are expressed in a wide range of organs and tissues. Mostly prominent in the liver, kidney and intestine; hence, reflecting their role in detoxification (Mazerska et al 2016;Liu et al, 2023). UGTs are also involved in epigenetic modifications such as DNA methylation and histone modifications, transcriptional regulation, post-transcriptional regulation (miRNA), and posttranslational regulation i.e.…”
Section: Insects and Glycosyltransferasesmentioning
confidence: 99%
See 1 more Smart Citation